An investigation of the longitudinal association of ownership of mobile phones and having internet access with intimate partner violence among young married women in India. - Thakkar, Shriya; Muhammad, T.; Maurya, Chanda (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Purpose: We explored the prevalence of intimate partner violence (physical, sexual, and emotional) and its longitudinal associations with the ownership of mobile phones and internet access among married women within the context of India. Methods: We used data from the longitudinal survey of "Understanding the Lives of Adolescents and Young Adults" (UDAYA-2015–16 and 2018–19) carried out in the two most populous states of India, Uttar Pradesh and Bihar. Descriptive statistics and random effects regression analysis were employed to determine the respective outcomes using a total sample of 20,700 participants across both states. Results: Percentages of women who reported ownership of mobile phones and internet access rose from 36.2% and 3.7% in wave 1 to 54.3% and 27% in wave 2, respectively. Despite increased ownership of technology, all forms of partner violence increased over time in this study. However, women who owned mobile phones were less likely to report physical [Coef: −0.041; p <.001] and sexual [Coef: −0.024; p <.001] violence, compared to those who had no mobile phones. Women who had internet access were negatively associated with physical [Coef: −0.048; p <.001], emotional [Coef: −0.034; p <.01], and any form of violence [Coef: −0.044; p <.001] than their counterparts. Conclusion: The findings underlined that internet access and ownership of mobile phones have been associated with improved safety and security for Indian women. The findings are important to practitioners, as they indicate that digital literacy among women should be promoted with immediate effect through the dissemination of workshops as well as strengthening availability and access to mobile phones and internet. This, in turn, would be a huge boost toward women's economic and social empowerment, particularly within the contemporary Indian context.